The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1158/1535-7163.mct-06-0216
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol-induced cyclooxygenase-2 facilitates p53-dependent apoptosis in human breast cancer cells

Abstract: Cyclooxygenase-2 (COX-2) is antiapoptotic and is implicated in tumorigenesis. Recent reports, however, have also ascribed a proapoptotic action to inducible COX-2. We show here for the first time that a stilbene, resveratrol, induces nuclear accumulation of COX-2 protein in human breast cancer MCF-7 and MDA-MB-231 cell cultures. The induction of COX-2 accumulation by resveratrol is mitogen-activated protein kinase (MAPK; extracellular signal -regulated kinase 1/2)-and activator protein 1-dependent. Nuclear COX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
116
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(122 citation statements)
references
References 41 publications
5
116
1
Order By: Relevance
“…34 The apoptosis is mediated by a mitochondrial-dependent pathway and calpain, a Ca +2 regulated protein, which also plays a role in the resveratrol-mediated apoptosis in MCF-7 cells. 34 Tang et al 35 reported that resveratrol induces nuclear accumulation of COX-2 protein in human breast cancer MCF-7 and MDA-MB-231 cell cultures, a process dependent on MAPK ½, and AP-1 eventually results in a p53-mediated apoptosis. The compound also decreases the telomerase activity in vitro.…”
Section: Breast Cancermentioning
confidence: 99%
“…34 The apoptosis is mediated by a mitochondrial-dependent pathway and calpain, a Ca +2 regulated protein, which also plays a role in the resveratrol-mediated apoptosis in MCF-7 cells. 34 Tang et al 35 reported that resveratrol induces nuclear accumulation of COX-2 protein in human breast cancer MCF-7 and MDA-MB-231 cell cultures, a process dependent on MAPK ½, and AP-1 eventually results in a p53-mediated apoptosis. The compound also decreases the telomerase activity in vitro.…”
Section: Breast Cancermentioning
confidence: 99%
“…Numerous studies have suggested that resveratrol may prevent the progression of various pathologies, including vascular diseases, ischemic injuries, cancer and neurodegenerative disorders (6)(7)(8). Furthermore, it has previously been confirmed that resveratrol exerts antiproliferative and/or apoptotic effects on leukemia, prostate, breast and colon cancers cells in vitro (9)(10)(11)(12). Previous studies regarding the anticancer effects of resveratrol have focused on its anti-invasive and anti-metastatic activities (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA was isolated as described previously (40). First-strand cDNAs were synthesized from 1 g of total RNA using oligo(dT) and AMV Reverse Transcriptase.…”
mentioning
confidence: 99%